Body composition and resting metabolic rate in obese adolescents - Oliveira, Bruno A. P. de; Gardim, Camila B.; Ferreira, Carolina N.; Cayres, Suziane U.; Freitas Junior, Ismael F. (Medicina (Ribeirao Preto), 2015)
Objective: Analyze body composition and resting metabolic rate (RMR) in obese adolescents. Methods: 58 obese adolescents were assessed between 12 and 16 years (13.7 ± 1.2 years). The body composition was measured dual-energy x-ray absorptiometry (DEXA). The resting metabolic rate and oxidation of glucose and lipids were determined by measuring the oxygen consumption and the production of carbon dioxide. Student t test was used for independent data, multiple linear regression and Pearson correlation, significance was set p <5%. Results: Significant differences were observed in the percentage of body fat (p = 0.01), percentage of lean body mass (LBM) (p = 0.01), percentage body fat (p = 0.01), lower limb lean mass (p = 0.01) and resting metabolic rate (p = 0.04) between males and females. The LBM is highlighted as the best predictor of RMR (p = 0.01). There was a positive correlation between RMR and LBM, as observed association between lipid oxidation and LBM. Conclusion: Total body composition and segment influence the resting metabolic rate and substrate oxidation. In addition, the LBM can be considered a factor of increased resting energy expenditure in obese adolescents.